2013
DOI: 10.9755/ejfa.v25i9.16394
|View full text |Cite
|
Sign up to set email alerts
|

Low cost medium formulation using cow dung ash for the cultivation of<br>Cyanobacterium: Spirulina (Arthrospira) platensis

Abstract: Spirulina (Arthroapira) characterized by helical/spiral shape in open left hand helix is a multicellular, free floating cyanobacterium or blue green alga. Its trichomes are cylindrical arranged in unbranched form and the width ranges from 6 to 12 µm. The basic helical feature of its filaments is unique and can be found only in liquid culture medium. Spirulina has been so popular in the world due to its high nutritional contents. It has been used as protein and vitamin supplement to the health food industry, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Also, tannins and saponins are capable of modifying the chemical synthesis of the microbe, inducing changes in the whole microbial fraction, methane production and microbial protein structure (Bhatta et al, 2009). Jain and Singh (2013) indicated the potentiality using of ruminants dung (cow ash) and Asmare et al (2014) from dairy manure to provide the nutrients to the culture medium that lower its high cost and make it economic culture for algal cultivation. Han et al (2016) proved that microalgae-bacteria cultures combination under mixotrophic conditions are also suitable effective strategy for microalgal cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…Also, tannins and saponins are capable of modifying the chemical synthesis of the microbe, inducing changes in the whole microbial fraction, methane production and microbial protein structure (Bhatta et al, 2009). Jain and Singh (2013) indicated the potentiality using of ruminants dung (cow ash) and Asmare et al (2014) from dairy manure to provide the nutrients to the culture medium that lower its high cost and make it economic culture for algal cultivation. Han et al (2016) proved that microalgae-bacteria cultures combination under mixotrophic conditions are also suitable effective strategy for microalgal cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce Spirulina production cost, dilutions of the modified ZM were tested and it was shown that modified ZM could be diluted up to five times without impacting the biomass productivity (Delrue et al, 2017). Furthermore, decomposed organic and inorganic nutrients media have been proven to be a good source of culture medium for Spirulina by many researchers (Markou and Georgakakis, 2011;Jain and Singh, 2013;Abdelhay et al, 2019). Hence, in the present study was aimed to investigate the effect of different vermicomposts incorporated with Zarrouk Medium (ZM) for the cultivation of Spirulina platensis.…”
Section: International Journal Of Zoological Investigationsmentioning
confidence: 99%
“…Toyub et al (2011) studied the growth performance of S. platensis in different concentrations of papaya (Carica papaya) skin powder media (PSPM), and maximum cell dry weight was found in control KM followed by 0.40 g/L of PSPM. Jain and Singh (2013) carried out an experiment to formulate a low-cost medium using different concentration gradients of cow dung ash medium (10-60%) and found 1.21 g/L dry biomass having 20% cow-dung ash supplemented with 80% prescribed medium. The results of above studies were consistent with the current findings, which point out the potential of BLAE comparing KM to reduce the cost of medium for S. platensis culture.…”
Section: Cell Dry Weightmentioning
confidence: 99%
“…By using inexpensive and easily accessible resources, the input costs for the commercial production of S. platensis can be decreased without impacting production efficiency. It has been demonstrated that decomposed organic and inorganic nutrients are reliable sources of nutrients for the cultivation of S. platensis (Habib et al, 2019;Jain and Singh, 2013;Sharker et al, 2007). It was found to be extremely cost-effective to modify the KM medium by substituting fertilizer grade MOP-K for potassium in commercial grade chemicals K 2 SO 4 (Akter et al, 2019).…”
Section: Introductionmentioning
confidence: 99%